2002
DOI: 10.1177/155005940203300409
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Quantitative EEG Response to Acute Caffeine Withdrawal: A Comprehensive Analysis of Multiple Quantitative Variables

Abstract: Most previous studies of the neurophysiological effects of caffeine have focused on the effects of caffeine ingestion, and few studies have examined the effects of caffeine withdrawal. This open study evaluated the quantitative EEG (QEEG) changes occurring during a 4-day period of abstinence in subjects who habitually consume 300 mg or more of caffeine daily. Thirteen subjects underwent QEEG studies during their usual caffeine consumption (baseline) and on days 1, 2, and 4 of a 4-day period of caffeine abstine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…However, across studies, findings have been inconsistent across different EEG measures. Changes in EEG have been demonstrated in studies comparing acute caffeine abstinence with a preceding baseline condition (Lader et al 1996;Reeves et al 2002) and a caffeine administration condition (Jones et al 2000).…”
Section: Impaired Behavioral and Cognitive Performancementioning
confidence: 97%
See 3 more Smart Citations
“…However, across studies, findings have been inconsistent across different EEG measures. Changes in EEG have been demonstrated in studies comparing acute caffeine abstinence with a preceding baseline condition (Lader et al 1996;Reeves et al 2002) and a caffeine administration condition (Jones et al 2000).…”
Section: Impaired Behavioral and Cognitive Performancementioning
confidence: 97%
“…Lane and PhillipsBute (1998) N=30 daily coffee consumers (mean 569 mg/day caffeine); within-subjects design; subjects were assessed on two occasions: after usual caffeine consumption and after overnight abstinence (estimated 12-28 h abstinence); abstinence not biologically verified Compared with ad libitum caffeine consumption, caffeine abstinence increased headache, drowsy/sleepy, irritable/cross/grumpy; fatigue (POMS), lethargy/fatigue/tired/sluggish, muzzy/foggy/not clearheaded, yawning, anger-hostility (POMS), confusion-bewilderment (POMS), depression-dejection (POMS), and decreased vigor (POMS), well-being, desire to socialize/talkativeness, ability to concentrate, energy/active, alert/attentive/observant; urge to do task/work-related activities; hot or cold spells, need to pass water d ; on a visual vigilance task abstinence decreased hit-rate and increased response time, and abstinence increased subjects ratings of perceived difficulty and decreased perceived importance of doing well and perceived success; after abstinence 47% reported any headache and 27% reported moderate or severe headache 57. Reeves et al (1995Reeves et al ( , 1997Reeves et al ( , 2002; Patrick et al (1996) N=13 or 14 daily caffeine users (>300 mg/day); within-subjects design; subjects evaluated while consuming their normal caffeine diet (baseline) and again after 1, 2, and 4 days of abstinence; evaluations included topographic quantitative EEG, physician ratings of caffeine withdrawal severity as assessed during a structured interview, and a musculoskeletal examination of the spine; abstinence was biologically verified Compared with baseline, significant quantitative EEG changes were: increase in theta absolute power, increase in delta absolute power over the frontal cortical areas, decrease in the mean frequency of both alpha and beta rhythm, increase in theta relative power, decrease in beta relative power, and change in interhemispheric coherence; resumption of caffeine following abstinence returned altered EEG values to baseline levels; all subjects reported caffeine-withdrawal symptoms and 77% had moderate or severe withdrawal severity as rated by a physician; compared with baseline, the number of somatic dysfunctions from the musculoskeletal examination was significantly greater on days 1, 2, and 4 of caffeine abstinence; the greatest number of somatic dysfunctions was reported on day 2; six subjects who had baseline EEGs containing diffuse paroxysmal slowing (DPS, a minor EEG dysrhythmia) showed significant increases in DPS firing during withdrawal and a return to baseline firing levels following caffeine resumption a All studies had a caffeine abstinence period of 12 h or greater b All effects are statistically significant at P≤0.05 unless otherwise noted c For consistency, when placebo and caffeine conditions are compared, the effects are described as the effects of placebo relative to caffeine d Likely a direct effect of caffeine rather than an effect of caffeine withdrawal e POMS indicates Profile of mood states questionnaire Dews et al (1999) N=6,815 adults who reported daily caffeine use were asked if they had "problems or symptoms on stopping caffeine in the past" 11% reported withdrawal symptoms upon stopping caffeine; of those, 25% reported symptoms severe enough to interfere with normal daily activities (e.g., lost time from work); headache was the most common symptom reported; it is unknown what percentage of daily users had ac...…”
Section: Driesbach and Pfeiffermentioning
confidence: 98%
See 2 more Smart Citations
“…In a recent follow-up study, Reeves, Struve, and Patrick (2002) gathered qEEG data while on caffeine, and then on days one, two, and four of caffeine withdrawal, and…”
mentioning
confidence: 99%